Oxidative damage and arginase activity in tissues of rats exposed to cigarette smoke - Yilmaz, S.; Benzer, F.; Ozan, S.; Gurgoze, S. Yaralioglu (Ecole Nationale Veterinaire Toulouse, 2008)
Oxygen free radicals generated in biological systems by cigarette smoke (CS) inhalation can cause oxidative stress in tissues, resulting in lipid peroxidation. To investigate whether cigarette smoking at different periods affect peroxidation speed, we examined concentrations of malondialdehyde (MDA) and activities of the catalase (CAT) and arginase in various tissues of rats exposed to CS. A total of 30 Wistar-Albino male rats were divided into 3 equal groups (n = 10): the rats of the groups I and II have inhaled CS for 30 and 60 minutes per day respectively for a total period of 3 months, whereas the rats of the group III served as controls. Significant increases of plasma, liver, heart, vessel, kidney, testis and oesophagus MDA concentrations were observed in the groups I and II, whereas brain, muscle and spleen MDA concentrations did not change compared to controls. Stomach MDA contents were significantly lowered in both treated groups. No statistically significant difference in plasma and in tissue MDA concentrations was observed between the 2 experimental groups except for vessel and stomach contents which were significantly more elevated in the group I than in the group II. While CAT activities in erythrocyte and lung tissues of the groups I and II increased, they significantly decreased in heart and kidney tissues. The arginase activities were significantly increased in heart and spleen in the both CS exposed groups, and in testis only in the group I, whereas they were depressed in lungs for the 2 groups, in stomach only in the group I and in brain only in the group II. These results suggest that the increased production of oxygen free radicals by CS may be responsible for an enhanced risk of various diseases related to cigarette smoking (lung and kidney cancers, cardiovascular diseases...) amplified by the CAT inactivation, while arginase activities seemed to be independent of MDA fluctuations and of CS exposure.
Keywords: cigarette smoke; plasma; tissue; malondialdehyde; catalase; arginase